Assessing the Impact of Early Childhood Education Programs on Cognitive, Social, and Emotional Development: A Quasi-Experimental Study - Rais, Rinovian; Haddar, Gamar Al (Insan Akademika Publications, 2024)
This research investigates the effectiveness of early childhood education programs in promoting early childhood development. Through a comprehensive study involving cognitive, social, and emotional domains, we assessed the impact of these programs on young children's developmental outcomes. Our findings reveal significant improvements in school readiness, problem-solving abilities, and social competence among children who participated in early childhood education programs compared to those who did not. These results underscore the enduring benefits of quality early education and highlight the importance of program quality, curriculum alignment with developmental milestones, and equitable access for all children. This research investigates the effectiveness of early childhood education programs in promoting holistic early childhood development. Through a quasi-experimental design, we analyzed the impact of these programs on cognitive, social, and emotional outcomes in young children. The results reveal significant positive effects, with program participants exhibiting improved school readiness, enhanced problem-solving skills, and greater social competence compared to their peers. These findings highlight the pivotal role of early education in equipping children with essential skills for academic achievement and socio-emotional well-being. Implications for policymakers emphasize the importance of equitable access to high-quality early education, curriculum development aligned with developmental milestones, and ongoing professional development for educators.